Economic Liberalisation and the Mobility of Minority Groups: Evidence from Māori in New Zealand - Isabelle Sin; Steven Stillman (Institute for the Study of Labor (IZA), 2015)
Between 1984 and 2003, New Zealand undertook comprehensive market-oriented economic reforms. In this paper, we use Census data to examine how the internal mobility of Māori compares to that of Europeans in New Zealand in the period after these reforms. It is often suggested that Māori are less mobile than other ethnic groups because of attachment to particular geographical locations. If this were the case, Māori may have been disadvantaged in the post-reform period because they were more likely to be living in adversely affected areas and less likely to move to pursue better employment opportunities. In contrast to the anecdotal evidence, we find that Māori are more mobile on average than similar Europeans. However, Māori who live in areas with strong networks of their iwi are slightly less mobile than Europeans. The difference between Māori who live locally to their iwi and those who do not is even more pronounced when we consider responsiveness to local labour market shocks. Non-local Māori are considerably more responsive to changes in economic opportunities than are Europeans, whereas local Māori are almost entirely unresponsive.
Keywords: J61; J15; R23; 330; mobility; migration; New Zealand; Māori; labour market areas